Competition in the Portuguese economy: insights from a profit elasticity approach - Jo\~ao Amador; Ana Cristina Soares (European Central Bank (ECB), 2013)
This article segments the Portuguese economy into fairly disaggregated markets and estimates a new competition measure suggested by Boone (2008), which draws on the concept of profit elasticity to marginal costs. In addition, robustness of results across econometric specifications is discussed, along with their consistency with classical competition indicators. The article concludes that the majority of Portuguese markets exhibited a reduction in competition in the period 2000-2009, though there is substantial heterogeneity. In addition, markets that faced competition reductions represent the large majority of sales, gross value added and employment in the Portuguese economy. The non-tradable sector shows lower competition intensity than the tradable sector. Moreover, reductions in competition are relatively widespread across markets in both sectors, but in terms of sales, gross value added and employment these reductions are more substantial in the non-tradable sector. In the majority of markets the assessment on the evolution of competition using profit elasticities is similar to that obtained with classical competition indicators.
Keywords: L10; L60; O50; 330; market competition; Portuguese economy